Urban Renewal and Displacement of Incumbent Residents: Evidence from Helsinki - Tuukka Saarimaa; Marika Ventovuori (Helsinki Graduate School of Economics, 2024)
We analyze displacement effects of a recent urban renewal program in Helsinki using population-wide register data and a difference-in-differences design. The data allow us to identify the incumbent residents in the program area and follow their later migration trajectories annually. We find that qualityadjusted housing prices increased in the targeted area by some 10–15% compared to control neighborhoods and that the program attracted higher income residents into new buildings built during the program's implementation. Incumbent public housing tenants and homeowners are more likely to stay in the targeted neighborhood after the program. We do not find evidence of displacement of incumbent tenants in market-rate rental housing. However, these results quite imprecise. These findings suggest that the program was successful in improving neighborhood quality and that incumbent public housing tenants and homeowners benefited from the program.
Keywords: I38; H31; R23; R28; 330; Place-based policy; residential displacement; urban renewal